METHODOLOGY OF TEACHING INFORMATION COMMUNICATION TECHNOLOGIES AND SYSTEMS IN THE ECONOMY IN HIGHER EDUCATION INSTITUTIONS BASED ON WEB TECHNOLOGIES - Yuldashev Shadiyor Shuxrat ogli; Bazarbayev Murotjon Xolmamat ogli (Bright Mind Publishing, 2025)
This article explores the methodology of teaching Information and Communication Technologies (ICT) and systems in economics at higher education institutions using web-based technologies. The study analyzes the implementation of digital infrastructure, distance learning tools, online platforms, and interactive teaching methods in economic education. Special attention is given to competency-based assessment systems, student-centered learning strategies, and the integration of practical tasks related to real-world economic scenarios.
Keywords: Information and communication technologies, web technologies, economic education, higher education, interactive learning, digital platforms, distance education.